Peer Phubbing and Social Networking Site Addiction: The Mediating Role of Social Anxiety and the Moderating Role of Family Financial Difficulty - Chu, Xiaoyuan; Ji, Shutian; Wang, Xingchao; Yu, Jingyue; Chen, Yuxin; Lei, Li (Frontiers in Psychology, 2021)
A growing body of research has pinpointed the consequences as well as mechanisms of phubbing. However, few studies have explored the relationship between peer phubbing and social networking site addiction. Based on the self-determination theory, the exclusion theory of anxiety, the social compensation model as well as the reserve capacity model, the present study examined whether peer phubbing was positively related to undergraduates’ social networking site addiction, whether social anxiety mediated the relationship, and whether this mediating process was moderated by family financial difficulty. Our theoretical model was tested using data collected from 1401 Chinese undergraduates (Mage = 18.83 years, SD = 0.93). Participants completed anonymous questionnaires assessing their peer phubbing, social anxiety, social networking site addiction, and family financial difficulty. Correlation analysis indicated that peer phubbing was positively associated with social networking site addiction. Testing for moderated mediation further revealed that social anxiety partially mediated the association between peer phubbing and social networking site addiction, with family financial difficulty moderating the first stage. To be specific, the indirect association between peer phubbing and social networking site addiction via social anxiety was stronger for undergraduates in high family financial difficulty. Results from this study extend research on the potential consequences of phubbing as well as highlight the significance of uncovering the underlying mechanisms.